2022
DOI: 10.1080/1359432x.2021.2023499
|View full text |Cite
|
Sign up to set email alerts
|

Job insecurity and employee performance: examining different types of performance, rating sources and levels

Abstract: We examine the relationship between job insecurity (JI) and performance (i.e., adaptivity, proactivity, task performance) from a multilevel perspective. We suggest that different behavioural responses will be triggered depending on whether the JI refers to an employee's relative JI within a team or a team's collective JI. An individual employee's relative JI within a team may evoke a withdrawal reaction (i. e., diminished performance) because the individual experiences the insecurity as a personal issue (one w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 78 publications
2
23
0
Order By: Relevance
“…They might engage in ERBs (i.e. actively praising and supporting their organization beyond the expected performance) only if they feel sufficiently motivated to do so by the positive inducement of their employer (Stynen et al, 2015), which might not be the case if they perceive that qualitative job insecurity is on the rise (Nikolova et al, 2022). If qualitative job insecurity is not viewed as something that deliberately targets employees' rewards, they might not see a reason to engage in fewer ERBs either, explaining our null finding.…”
Section: Discussionmentioning
confidence: 99%
“…They might engage in ERBs (i.e. actively praising and supporting their organization beyond the expected performance) only if they feel sufficiently motivated to do so by the positive inducement of their employer (Stynen et al, 2015), which might not be the case if they perceive that qualitative job insecurity is on the rise (Nikolova et al, 2022). If qualitative job insecurity is not viewed as something that deliberately targets employees' rewards, they might not see a reason to engage in fewer ERBs either, explaining our null finding.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, there is limited knowledge about the impact of JIS on employees' PEBs. As a matter of fact, there is limited research about the impact of JIS on performance-related outcomes [10]. Excluding Karatepe's [4] work which reported that JIS impeded hotel employees' green recovery performance and proactive PEBs, past and recent writings do not shed light on whether employees suffering from the threat of job loss in the future do not contribute to the hotel's environmental sustainability efforts through their PEBs [23,24].…”
Section: Contributionmentioning
confidence: 99%
“…One of the most critical hindrance stressors in today's competitive market environment that may hamper employees' proactive PEBs is job insecurity (JIS) [4]. JIS, which highlights the "…perceived powerlessness to maintain desired continuity in a threatened job situation" [5, p. 438], is prevalent in many industries including the hospitality and tourism industry [6][7][8][9][10][11], and has been intensified by the COVID-19 pandemic [12][13][14]. Employees suffering from heightened JIS exhibit emotional exhaustion [13], which denotes the depletion of emotional resources as a result of excessive job demands [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also aimed to enhance more clarity on the factors that could determine the outcome of these appraisal processes. On the one hand, it has been suggested that the more job insecurity is perceived as an individual or personal problem rather than a collective one, the more it may be perceived as threatening and associated with reduced performance 25 . On the other hand, it has been suggested that also negative emotions such as fears in the broader context of job insecurity may play a role (e.g., fear that the company would close, fear that the company would not obtain its goals).…”
Section: Learning Outcomesmentioning
confidence: 99%
“…On the one hand, it has been suggested that the more job insecurity is perceived as an individual or personal problem rather than a collective one, the more it may be perceived as threatening and associated with reduced performance. 25 On the other hand, it has been suggested that also negative emotions such as fears in the broader context of job insecurity may play a role (e.g., fear that the company would close, fear that the company would not obtain its goals). Emotions, such as fears, are based on contextual information but also serve as a guide for deciding which behavior will be enacted.…”
Section: Job Insecurity and Job Performancementioning
confidence: 99%